Dual action of Dooku1 on PIEZO1 channel in human red blood cells - Hatem, Aline; Poussereau, Gwendal; Gachenot, Martin; Pérès, Laurent; Bouyer, Guillaume; Egée, Stéphane (Frontiers in Physiology, 2023)
PIEZO1 is a mechanosensitive non-selective cation channel, present in many cell types including Red Blood Cells (RBCs). Together with the Gárdos channel, PIEZO1 forms in RBCs a tandem that participates in the rapid adjustment of the cell volume. The pharmacology allowing functional studies of the roles of PIEZO1 has only recently been developed, with Yoda1 as a widely used PIEZO1 agonist.In 2018, Yoda1 analogues were developed, as a step towards an improved understanding of PIEZO1 roles and functions. Among these, Dooku1 was the most promising antagonist of Yoda1-induced effects, without having any ability to activate PIEZO1 channels. Since then, Dooku1 has been used in various cell types to antagonize Yoda1 effects. In the present study using RBCs, Dooku1 shows an apparent IC50 on Yoda1 effects of 90.7 µM, one order of magnitude above the previously reported data on other cell types. Unexpectedly, it was able, by itself, to produce entry of calcium sufficient to trigger Gárdos channel activation. Moreover, Dooku1 evoked a rise in intracellular sodium concentrations, suggesting that it targets a non-selective cation channel. Dooku1 effects were abolished upon using GsMTx4, a known mechanosensitive channel blocker, indicating that Dooku1 likely targets PIEZO1.Our observations lead to the conclusion that Dooku1 behaves as a PIEZO1 agonist in the RBC membrane, similarly to Yoda1 but with a lower potency. Taken together, these results show that the pharmacology of PIEZO1 in RBCs must be interpreted with care especially due to the unique characteristics of RBC membrane and associated cytoskeleton.